Thermal ecology and baseline energetic requirements of a large‐bodied ectotherm suggest resilience to climate change. Issue 12 (7th May 2021) - Crowell, Hayley L.; King, Katherine C.; Whelan, James M.; Harmel, Mallory V.; Garcia, Gennesee; Gonzales, Sebastian G.; Maier, Paul H.; Neldner, Heather; Nhu, Thomas; Nolan, John T.; Taylor, Emily N.
Abstract: Most studies on how rising temperatures will impact terrestrial ectotherms have focused on single populations or multiple sympatric species. Addressing the thermal and energetic implications of climatic variation on multiple allopatric populations of a species will help us better understand how a species may be impacted by altered climates. We used eight years of thermal and behavioral data collected from four populations of Pacific rattlesnakes ( Crotalus oreganus ) living in climatically distinct habitat types (inland and coastal) to determine the field‐active and laboratory‐preferred body temperatures, thermoregulatory metrics, and maintenance energetic requirements of snakes from each population. Physical models showed that thermal quality was best at coastal sites, but inland snakes thermoregulated more accurately despite being in more thermally constrained environments. Projected increases of 1 and 2°C in ambient temperature result in an increase in overall thermal quality at both coastal and inland sites. Population differences in modeled standard metabolic rate estimates were driven by body size and not field‐active body temperature, with inland snakes requiring 1.6× more food annually than coastal snakes. All snakes thermoregulated with high accuracy, suggesting that small increases in ambient temperature are unlikely to impact the maintenance energetic requirements of individual snakes and that some species of large‐bodied reptiles may be robust to modest thermal perturbations under conservative climate change predictions. ​ Abstract : We used long‐term thermal data collected from four populations of Pacific rattlesnakes ( Crotalus oreganus ) to determine and compare thermoregulatory metrics and maintenance energetic requirements of snakes living in climatically distinct habitats (coastal and inland). Thermal quality was best at coastal sites, but inland snakes thermoregulated more accurately despite being in more thermally constrained environments. Population differences in standard metabolic rate estimates were driven by body size rather than body temperature, with inland snakes requiring 1.6× more food annually than coastal snakes. ​